Comparative evaluation of microelements' balance in the organism of fertile men on the ecocontrast territories (Environment & Health, 2015)
In modern conditions a human need for micronutrients has increased substantially that causes the increased attention of the scientists to the problem of optimal body's provision of essential microelements, a balance of biotic and abiotic metals, their effect on human health, including reproductive.Objective. We identified the features of microelements' content in biosubstrates of fertile men residing in the cities of the Dnipropetrovsk oblast with different levels of technogenic contamination of the environment.Materials and methods. The content of microelements of heavy metals' group (Pb, Cd, Cu, Zn) in a whole blood and ejaculate was determined by the inversion voltamperometry in two groups of relative "healthy" men with normal fertility, residing in the industrial city, and in a control one, in the conditionally "pure" city. In addition, we calculated the index of metals' penetration through the hematotesticular barrier and coefficients of their proportion.Results. The content of lead and cadmium in biosubstrates of fertile men of the industrial territories, meets, on average, the standard level, though it is 1.2-10.0-fold higher than analogous indices of conventionally "clean" areas. The content of lead in men's blood is 1.2-fold higher in comparison with its concentration in the ejaculate. The concentration of copper in the men's biosubstrates meets the physiological parameters relative to a whole blood, though it increases 1.2-1.6-fold the analogous indices of the mineral composition of the ejaculate. On average, zinc concentration makes up (84.94±2.27) mg/l in the ejaculate of all the examined men, it is 30.2-fold higher in comparison with its level in the whole blood and indicates the exceptionally important role of zinc in the process of spermatogenesis and the formation of fertile properties of ejaculate. At the same time its content in biosubstrates of men, residing under conditions of increased technogenic load, is 2-1.9-fold lower in comparison with the physiological level, it may indicate a probability of the development of zinc deficit state in this group of the population. Coefficients of the proportion of the majority of the metals indicate a pronounced imbalance of microelements in the organism. At the same time, the ejaculate is the most informative test-object for the early detection of the disorders in microelement homeostasis and pre-nosologic changes in male generative sphere.
Keywords: heavy metalsbiomonitoringbloodejaculatefertile menmicroelements' balance